Key success factors for adoption of Cloud Computing services - Jerkovič, Martin; Feuerlicht, Jiří; Burkoň, Lukáš; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2011)
Bachelor Thesis deals with one of the biggest phenomenom of latest times in IT world -- cloud computing. Cloud computing is still "buzzword" and thus first part of Bachelor Thesis defines fundamentals, classification and characteristics of this revolutionary solution. Second part is analytical and it covers the biggest issues that come with adoption of cloud services such as security, compliance, IT organization and many others. Results of comprehensive analysis are used in third part which is the most important. It lists key success factors for adoption of cloud services which is also an objective of Thesis. They are defined as set of recommendations with brief description.
Vedoucí práce: Jiří Feuerlicht
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2011
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2011
Způsob přístupu: Internet
Keywords: informatika [obor bakal. práce]; bakalářské práce; bachelor's theses